Intravitreal dexamethasone versus bevacizumab in Aboriginal and Torres Strait Islander patients with diabetic macular oedema: The OASIS study (a randomised control trial). (8th April 2022) - Meyer, Joos; Fry, Carly; Turner, Angus; Razavi, Hessom
Abstract: Background: Frequent intravitreal anti‐VEGF injections are impractical for many Aboriginal patients with diabetic macular oedema (DMO). The longer acting intravitreal dexamethasone implant (DEX‐implant) is approved for DMO but has not been assessed in an Aboriginal population. Methods: This was a prospective, multicentre, randomised, single‐masked, non‐inferiority clinical trial. Aboriginal adults from Western Australia with DMO were randomised to receive 3‐monthly DEX‐implant, or monthly intravitreal bevacizumab. The primary outcome was the change in best corrected visual acuity (BCVA) at 12 months. Results: The final endpoint was analysed for 24 DEX‐implant and 28 bevacizumab injection eyes. Mean BCVA improved by 4.0 letters (−0.08 LogMAR) in the DEX‐implant group and worsened by 5.5 letters (0.11 LogMAR) in the bevacizumab group. Before adjusting for cataract surgery, the upper bound of the two‐sided 90% CI for the DEX‐implant was 3.5 letters (0.07 LogMAR), which met non‐inferiority criteria. The BCVA of remote participants who received the DEX‐implant improved by 5.5 letters (0.11 LogMAR), compared to an 18.5 letter (0.37 LogMAR) decline for bevacizumab ( p  = 0.04). The incidence of steroid‐induced ocular hypertension for the DEX‐implant was 33.3%. Conclusions: Before adjusting for the effect of cataract surgery, the DEX‐implant was non‐inferior to bevacizumab for treating DMO in Aboriginal participants. In remote participants, the DEX‐implant surpassed non‐inferiority to achieve superior outcomes to bevacizumab. The incidence of steroid‐induced hypertension was comparable to that reported in non‐Aboriginal populations. We provide guidelines for the judicious use of DEX‐implant among Aboriginal people, and a framework for performing ophthalmic clinical trials in Aboriginal communities.